WILL OSHA BAR THE DOOR TO WORKPLACE SMOKING? CONGRESS CONSIDERS INDOOR AIR BILLS - LABAR,G (Tufts Archival Research Center, 2007)
Article regarding OSHA's response to demands for smoking restrictions in buildings. Describes the two possible solutions OSHA has come up with as implementing a smoking specific health standard or incorporating it into an indoor air quality standard. Quotes tobacco industry representatives as saying that second hand smoke is not known to be the cause of any disease and that therefore a ban is premature. Points out that most employers already have some smoking policy in place, and cite concerns or litigation and increased health costs as the reason.